An analysis of income inequality in eight regencies and cities in Banten using panel data - Muhammad Hanif Mufid; Dini Yuniarti; Rifki Khoirudin (Optimum: Jurnal Ekonomi dan Pembangunan, 2026)
Income inequality remains a major challenge for regional economic development, particularly in Banten Province, which is characterized by pronounced regional disparities driven by urbanization and economic agglomeration. This phenomenon is influenced by various economic and social factors that have not yet been comprehensively examined within the regional context of Banten.  Research on income inequality in Banten is therefore essential, as rapid economic growth concentrated in industrial areas has not necessarily translated into an equitable distribution of welfare across regencies and cities. This study aims to analyze the effects of economic growth, the Human Development Index (HDI), minimum wage, number of firms, and poverty rate on income inequality in eight regencies and cities in Banten Province over the period 2011–2023. The study employs a quantitative approach using panel data regression, combining both time-series and cross-sectional data. The results indicate that HDI has a positive and statistically significant effect on income inequality. In contrast, minimum wage, number of firms, and poverty rate exhibit significant negative effects on income inequality, while economic growth does not have a statistically significant impact. These findings are expected to provide valuable insights for local governments in designing policies that promote more equitable economic development and reduce income inequality in Banten Province.